USE OF CANVA APPLICATION IN LEARNING PANCASILA AND CITIZENSHIP EDUCATION - Muhammad Kenzie; Hannan Rava Mahardika; Muhammad Faiz Hariy Nughroho; Muhammad Fabian Pratama (PT. Radja Intercontinental Publishing, 2024)
Pancasila and Citizenship Education (PPKn) has a strategic role in shaping students' character in accordance with the values ​​of Pancasila. However, the abstract and normative nature of the material often leads to a lack of student interest. This study aims to explore the use of Canva application as a technology-based learning media in Civics subject. Using qualitative research methods, data was collected through interviews with subject teachers and analysis of students' poster assignments. The results showed that the use of Canva significantly improved students' understanding of Pancasila values ​​and honed 21st century skills such as creativity and critical thinking. Teachers assessed students' assignments based on content and design creativity, which helped students convey information in an interesting and relevant manner. Despite challenges such as limited internet access and technical skills, the app proved effective in supporting interactive learning. It is recommended that regular technical training and supporting facilities be provided to optimize the use of Canva in Civics learning.